Sourcing strategies in a pandemic: an analysis of LS fashion's import of garment fabrics from China during Covid-19 - Ahmed, Osman Bin (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.